Analisis Tindak Pidana Korupsi dalam Korelasi Tafsir Hukum pada Ayat Pencurian - Aziz, A. Fauzi; Afifudin, Lukman (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2024)
Legal interpretation aims to comprehend and apply the law contained within verses of the Quran. One such verse, Surah Al-Maidah, Ayah 38, discusses theft-related punishment. This verse has been interpreted by various scholars, both classical and contemporary, from diverse perspectives and methodologies. This study aims to analyze and compare the interpretations of the law on theft-related verses in correlation with corruption, a criminal act that damages the state's finances. The research adopts a qualitative method using a literature review approach. The data used consists of tafsir books, articles, journals, and relevant legal documents. The findings reveal differences and similarities between classical and contemporary scholars in interpreting the law on theft. Classical ulama tend to adhere to a literal and textual understanding of the verse, prescribing the punishment of cutting off the hand without differentiating the type or value of the stolen item. Contemporary ulama tend to utilize contextual and rational approaches, allowing theft punishments to vary based on societal conditions and situations. Concerning corruption, some contemporary ulama consider it within the theft category, thus advocating punishments such as hand amputation or equivalent penalties. Other contemporary ulama argue that corruption does not fall under theft, hence its punishment should align with prevailing positive law provisions. Furthermore, the correlation between Surah Al-Maidah, Ayah 38, and corruption lies in aspects like: (1) illegal acquisition of wealth, (2) detrimental effects on society and (3) detrimental effects on state.